RISK FACTORS OF CHRONIC KIDNEY DISEASE AMONG INDONESIAN PROSPECTIVE HAJJ PILGRIMS (DATA ANALYSIS OF SISKOHATKES 2024): Faktor Risiko Gagal Ginjal Kronis pada Calon Jemaah Haji Indonesia (Analisis Data Siskohatkes 2024) - Kusumastuti, Istyarahma Kansya; Simanjorang, Chandrayani; Laily Hanifah; Budianto, Heri (Universitas Airlangga, 2025)
Background: Chronic Kidney Disease (CKD) is an escalating global public health issue. By 2024, CKD ranked sixth among the top ten causes of death among Indonesian hajj pilgrims and served as a comorbidity for the two leading causes of mortality, hypertension and cardiovascular diseases. Purpose: This study aims to identify the risk factors of CKD among Indonesian prospective hajj pilgrims in 2024. Methods: A cross-sectional design was utilized using secondary data from the Integrated Hajj Computerized System for Health Sector (Siskohatkes) for all registered pilgrims in 2024. A total of 217,476 participants were enrolled using purposive sampling. Data were analyzed using multivariate logistic regression. Results: The prevalence of CKD among prospective Indonesian hajj pilgrims was 0.2%. Multivariate analysis revealed significant risk factors, including family history of CKD (aPOR = 3.51; 95% CI: 1.30–9.48), diabetes mellitus (aPOR = 2.25; 95% CI: 1.82–2.78) male (aPOR = 2.10; 95% CI: 1.71–2.57), age ≥ 60 years (aPOR = 1.93; 95% CI: 1.48–2.52), and hypertension (aPOR = 1,90; 95% CI: 1,48–2,44). Conclusions: This study highlights risk factors for CKD among prospective Indonesian hajj pilgrims, with a family history of CKD being the most dominant risk factor. The Indonesian Hajj Health Center is advised to standardize the diagnostic methods for CKD and integrate health information systems to serve as a reference for comparison of examination results.